Knowledge, Attitude, and Conservation Intention of Snake: A Study on IPB University Students’ Perception - Loar, Loise Liberta; Kusrini, Mirza Dikari; Meilani, Resti (Media Konservasi, 2025)
Twenty-nine species of snakes, eight highly venomous, inhabit various habitats found in the IPB Darmaga Campus, posing risks to people who have activities on campus. A snake bite case occurred on the IPB Darmaga campus in 2021, causing death. Such a case can incite negative perceptions in people and adversely affect their conservation intention. This study aimed to analyse students' knowledge and attitudes about snakes on the IPB Darmaga campus and draw on their conservation intentions from the data. A Google form was used to collect the data from 374 respondents from nine faculties at IPB University. A comparison was made between the students actively joining the Herpetofauna Observation Group (KPH) and the general students (non-KPH). Knowledge of the presence of snakes on campus was strongly influenced by information availability and student activities. All KPH students had direct encounters with snakes on campus, while only 52.9% of non-KPH students had such encounters. A total of 7.2% of non-KPH students and 58.6% of KPH students correctly identified the types of venomous and non-venomous snakes. Some non-KPH students were afraid of and disgusted by the sight of snakes. In contrast to KPH students, most non-KPH students suggested they would kill snakes upon encounter, showing their lack of conservation intention. Such data suggests the need for snake education for students to improve their conservation intention of the species, while at the same time increasing their ability to protect themselves from the risk of conflicts.